The efficacy of mindfulness-based interventions on mental health among university students: a systematic review and meta-analysis - Zuo, Xinyi; Tang, Yong; Chen, Yifang; Zhou, Zhimiao (Frontiers in Public Health, 2023)
We aimed to estimate the effect of mindfulness therapy on mental health. Two researchers searched twelve databases to identify relevant trials that were published from 1 January 2018 to 1 May 2023. We performed a meta-analysis to determine the effect of mindfulness therapy on depression, which was measured by the Beck Depression Inventory (BDI), Patient Health Questionnaire-9 (PHQ-9), Quick Inventory of Depressive Symptomatology (QIDS), Hamilton Depression Rating Scale (HDRS), Patient-Reported Outcomes Measurement Information System (PROMIS), Hospital Anxiety and Depression Scale (HADS), and Depression Anxiety Stress Scales (DASS); anxiety, which was measured by the Beck Anxiety Inventory (BAI), PROMIS, and DASS, Generalized Anxiety Disorder-7 (GAD-7); stress, which was measured by the Perceived Stress Scale (PSS), DASS, and GAD-7; mindfulness, which was measured by the GAD-7, Five Facet Mindfulness Questionnaire (FFMQ), Mindful Attention Awareness Scale (MAAS), Short Form-12 Mental Component Score (SF-12 MCS) and Short Form-12 Physical Component Score (SF-12 PCS); and sleep quality, which was measured by the Pittsburgh Sleep Quality Index (PSQI). After screening studies based on the inclusion and exclusion criteria, eleven randomized controlled trials (RCTs) involving 1824 participants were ultimately included. All these studies demonstrated positive effects of mindfulness therapy on depression (MD=−0.33, 95% CI: [−0.44, −0.22], P ＜ 0.00001, I2=29%) , anxiety (MD=−0.35, 95% CI: [−0.46, −0.25], P ＜ 0.00001, I2=40%) and stress (MD=−0.39, 95% CI: [−0.48, −0.29], P ＜ 0.00001, I2=69%). However, there was no significant difference in mindfulness (MD=−0.12, 95% CI: [−0.36, −0.12], P=0.34, I2=34%) or sleep quality scores (MD=−0.81, 95% CI: [−1.54, −0.09], P=0.03, I2=0%) between the mindfulness therapy group and the control group. In future studies, it is necessary to consider the investigation on whether the strategies of improving the mindfulness therapy in adherence and fidelity can work on the improvement of the outcomes in mental health.